2009
DOI: 10.1002/jso.21299
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of the number of lymph nodes retrieved after neoadjuvant chemoradiotherapy with mesorectal excision for rectal cancer

Abstract: In a neoadjuvant setting, ypN(+) disease was an independent risk factor for oncological outcomes. An absence of nodes does not represent an inferior oncological outcome. The number of nodes does not seen to impact survival and recurrence in ypN(-) patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
(35 reference statements)
0
26
0
1
Order By: Relevance
“…After manual dissection, the absence of LNs (ypNx) was related to favorable prognosis similar to the outcome of node-negative patient (ypN) cases. 20 FIGURE 5. Effect of AC on LN size.…”
Section: Discussionmentioning
confidence: 99%
“…After manual dissection, the absence of LNs (ypNx) was related to favorable prognosis similar to the outcome of node-negative patient (ypN) cases. 20 FIGURE 5. Effect of AC on LN size.…”
Section: Discussionmentioning
confidence: 99%
“…The mean number of harvested lateral pelvic lymph nodes was more in the laparoscopic group than in the open group (19.5 vs. 15.8, P < 0.05). In lateral pelvic lymph node dissection following neo-adjuvant chemo-radiotherapy, lymph node yield would be low [63] and studies have shown that the number of lymph nodes does not affect the recurrence rate and survival [64] . Furuhata et al [65] confirmed the good oncological outcomes with perioperative morbidity of 16.7% as three patients developed grade 2 urinary retention.…”
Section: Lateral Pelvic Lymph Node Dissectionmentioning
confidence: 99%
“…Invasion of blood vessels within the bowel wall is defines as intramural BVI and invasion of blood vessels outside the bowel wall (per colonic fat or subserosal fat) is defined as extramural BVI invasion [17][18][19]. Both Talbot et al [9] and Minsky et al [6] found that the extramural component of blood vessel invasion was not predictive of survival.…”
Section: Discussionmentioning
confidence: 99%